A teoria austríaca dos ciclos econômicos: uma análise para a economia brasileira, 2004-2019 - Barros, Augusto Luiz Heck (2020)
The Austrian Theory of Business Cycles is the theory of the unsustainable boom. The policy of artificial credit expansion central bank distorts interest rates and lead to an intertemporal misallocation of capital, thereby creating artificial expansion. Eventually the central bank is forced to restrict expansionary monetary policy due to the inflationary pressure caused by the general resource constraint, revealing the process of capital misallocation. Several unprofitable investments must be liquidated, marking the beginning of the economic recession phase. The study implements Toda-Yamamoto (1995) approach for testing Granger causality and Almon (1965) polynomial distributed-lag method to identify whether the cyclical fluctuations in the Brazilian economy between 2004 and 2019 can be explained by Austrian Theory of Economic Cycle. The main results found that support Mises-Hayek's theory of business cycles are: (1) the artificial expansion in the credit supply occurred through subsidized loans and was not based on the increase in society's saving rate, (2) changes in the money supply have effects on changes in the spread of interest rates, which, in turn, have an impact only on sectoral and aggregate industrial production, but not on gross domestic product, and (3) strong evidence that manipulation of the money and credit supply directly affects the economy's production structure and gross domestic product and has an influence on the cyclical pattern observed in aggregate industrial production and gross domestic product.